RETRACTED: Integrated recycling of wood waste using recycling technology - Petrova A.A.; Zyryanov M.A.; Medvedev S.O.; Voronin I.A.; Petrova I.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001